One Health Initiative: Agrovet Shop Survey Dataset - Rheman, Shafiq; Khor, Laura; Verner-Jeffreys, David; Hossain, Sabrina; Delamare-Deboutteville, Jerome (2024)
We conducted discussions with agrovet business to generate data needed for a study on economic and social aspects of using aquamedicines. Shops were randomly selected to participate in this discussion. Some specific questions were asked regarding practices, knowledge and sales of veterinary medicines.